Development of Audiovisual Educational Media Based on Animated Videos about Food Sanitation Hygiene for Catering Food Handlers - Dita Ayu Safitri; Karpin Karpin; Rita Patriasih (Universitas Pendidikan Indonesia (UPI), 2023)
Food safety refers to the safe handling, processing and distribution of food ingredients to prevent food borne illness. One aspect related to food safety is food sanitation hygiene. So that the handlers food needs to have knowledge related to food sanitation hygiene. Food sanitation hygiene is an effort to control factors that cause disease through food. Thus, it is important to educate food handlers about food sanitation hygiene, one of which is through the media. Media that can be used in education include animated videos. The aim of this research is to develop audiovisual educational media based on animated videos about food sanitation hygiene for food handlers in catering. Research and Development level 1 is used as a research method in developing this media. This research was conducted to produce animated videos that went through the stages of media design, media development, and validation through three aspects, namely media aspects, material aspects, and language aspects. The results of this research are in the form of an animated food sanitation hygiene video which has been validated by experts who stated that the media developed is suitable and can be used for catering food handlers. Recommendations for future researchers are that food sanitation hygiene animation media can be tested on food handlers in catering.